Developing English Syllabus for Pharmacy Students - Edi Suwandi; Khoirul Wafa (Institut Agama Islam Negeri Palopo, 2020)
Starting with the Hutchinson and Walter (1994:18) that said if ESP is an approach to language learning based on the students’ need. Moreover, knowing the reason for the students learn English is the fundamental reason. As the writer’s experience to teach English in Pharmacy Unugiri Bojonegoro that there was no developed syllabus based on the students’ need but only based on the lecturer’ experience and knowledge. This research was at knowing the students’ need and developing it to English in pharmacy syllabus. The procedures are to break down , to depict the purpose for the syllabus, to choose the syllabus type, to compose the syllabus content, to validate the created syllabus with the expert , to assess and redesign the syllabus. The subject of this study were fifty students of the second semester of the pharmacy program at Unugiri Bojonegoro that consist of 44 female and 6 male students and an English lecturer. Besides that some questioners were given to the students. The result of this study shows that if the students need the topics that related their future career and real life in their environment. The last result for this research is English in Pharmacy syllabus for bachelor students of Pharmacy program at Unugiri Bojonegoro.